(NpRONIKA@]AQ TURBULENTNAQ KONWEKCIQ (B/s - (NzILITINKEWI^(B, (NsERGEJ sERGEEWI^s; (NrAUKAS(B, (Na(B.(Nw(B.s ((NtALLINN (B:s (NwALGUS(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 193-207s
(Nan |ssr(B, (N|ST(B. (NGEOGR(B. (NO(B-(NWOs
Keywords: (NkONWEKCIQs; (NpOGRANI^NYJ SLOJ TURBULENTNYJs